Rapid and Synchronous Breeding of Cytoplasmic Male Sterile and Maintainer Line Through Mitochondrial DNA Rearrangement Using Doubled Haploid Inducer in Brassica napus - Zhang, Wei; Shi, Haoran; Zhou, Ying; Liang, Xingyu; Luo, Xuan; Xiao, Chaowen; Li, Yun; Xu, Peizhou; Wang, Jisheng; Gong, Wanzhuo; Zou, Qiong; Tao, Lanrong; et al. (Frontiers in Plant Science, 2022)
When homozygously fertile plants were induced using double haploid (DH) induction lines Y3380 and Y3560, the morphology of induced F1 generation was basically consistent with the female parent, but the fertility was separated, showing characteristics similar to cytoplasmic male sterile (CMS) and maintainer lines. In this study, the morphology, fertility, ploidy, and cytoplasm genotype of the induced progeny were identified, and the results showed that the sterile progeny was polima cytoplasm sterile (pol CMS) and the fertile progeny was nap cytoplasm. The molecular marker and test-cross experimental results showed that the fertile progeny did not carry the restorer gene of pol CMS, and the genetic distance between the female parent and the offspring was 0.002. This suggested that those inductions produced sterile and fertile progeny were coordinated to CMS and maintainer lines. Through the co-linearity analysis of the mitochondrial DNA (mtDNA), it was found that the rearrangement of mtDNA by DH induction was the key factor that caused the transformation of fertility (nap) into sterility (pol). When the induction of heterozygous maternal using DH inducer resulted in the segregation of fertility in the induced F2 generation, and the average genetic distance between sterile and fertile plants was 0.075. It is the potential to rapidly and synchronously achieve the CMS and maintainer lines of different cytoplasm through sister-crosses and self-crosses. The induction of DH inducer in B. napus can provide a new model for the innovation of germplasm resources and open up a new way for its application.